Associations between spouse and service member prescriptions for high-risk and long-term opioids: A dyadic study. (December 2021) - Sparks, Alicia C.; Radakrishnan, Sharmini; Corry, Nida H.; McDonald, Doug; Carlson, Kenneth; Carballo, Carlos E.; Stander, Valerie
Highlights: Military spouses were more likely to have risky opioid Rx if their spouse did. High-risk opioid therapy was linked to pain, disability, smoking, and ACES Reducing risky opioid Rx for service members may reduce similar risky Rx for spouses. Abstract: Background: Estimates suggest approximately 2.4% of service members, and 15% of service members who have engaged in recent combat, report misusing pain relievers in the past year. This study explores the extent to which military spouses' obtainment of opioids is associated with their service member partners' obtainment of opioid prescriptions, in addition to other factors such as service member health, state prescribing patterns, and sociodemographic characteristics. Methods: Data were drawn from the Millennium Cohort Family Study, a large, longitudinal survey of married spouses of service members from all service branches, and archival data analyzed from 2018 to 2020. The dependent variables were spouse long-term opioid therapy and spouse opioid prescriptions that pose a high risk of adverse outcomes. Results: Seven percent of spouse and service member dyads met the criteria for high-risk opioid use, generally because they had purchased a prescription for a ≥90 Morphine Milligram Equivalents daily dose (76.7% for spouses, 72.8% for service members). Strong associations were found between spouse and service member opioid therapies (OR = 5.53 for long-term; OR = 2.20 for high-risk). Conclusions: Findings suggest that reducing the number of long-term and high-risk opioid prescriptions to service members may subsequently reduce the number of similar prescriptions obtained by their spouses. Reducing the number of service members and spouses at risk for adverse events may prove to be effective in stemming the opioid epidemic and improve the overall health and safety of military spouses and thus, the readiness of the U.S. Armed Forces.